2007
DOI: 10.3177/jnsv.53.109
|View full text |Cite
|
Sign up to set email alerts
|

The Application of a Handheld Personal Digital Assistant with Camera and Mobile Phone Card (Wellnavi) to the General Population in a Dietary Survey

Abstract: Summary This study was carried out to examine first, the validity of a new dietary assessment method, a handheld personal digital assistant with camera and mobile phone card (Wellnavi), in comparison with a weighed diet record as a reference method and second, the relation between obesity and underreporting in the Wellnavi method in 27 men and 48 women volunteers aged 30-67 y from the general population. On the validity, there were significant correlations (0.32-0.75) between the daily nutrient intakes measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
4
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 23 publications
6
84
4
2
Order By: Relevance
“…There have been a number of reported studies using camera technology in dietary analysis (30)(31)(32)(33)(34)(35) , some of which have shown similar improvements in under-reporting; however, the majority of these studies involve the consumer capturing the image of the meal. Therefore, the choice remains as to whether the consumer records the eating episode and the problem of underreporting also remains.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of reported studies using camera technology in dietary analysis (30)(31)(32)(33)(34)(35) , some of which have shown similar improvements in under-reporting; however, the majority of these studies involve the consumer capturing the image of the meal. Therefore, the choice remains as to whether the consumer records the eating episode and the problem of underreporting also remains.…”
Section: Discussionmentioning
confidence: 99%
“…Mobile computing devices such as personal digital assistants (PDAs) and smart phones with cameras are poised to show their potential as a general purpose computing device. PDAs are ideal as a field data collection device (Wang et al, 2002;Kretsch et al, 2004;Kikunaga et al, 2007). In 2004, a survey by Quality Education Data Inc. found that 28% of US school districts offered handheld computers for student and teacher use (Burke, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an accurate assessment of nutrition habits is of growing importance. Though traditional measurement methods are improving and new techniques are developed [16][17][18][19][20], the complexity of nutrition intake naturally leads to errors in its assessment. Comprehensive information about nutrition habits would include a multitude of different factors, such as portion size of foods, frequency of consumption, food composition, daily variations in food intake and many more.…”
Section: Introductionmentioning
confidence: 99%